Importancia del ambiente familiar en el desarrollo cognitivo del niño en nivel inicial 2 en la Unidad Educativa “Semillitas Life School”, Cuidad de Riobamba - Salazar Miranda, Yudi Alexandra (2024)
The purpose of this research project is to demonstrate the importance of the family environment in children's cognitive development at the initial level 2 of the "Semillitas Life School" Educational Unit. It is a crucial topic that has been the subject of research and reflection in the educational field. The population in this research consists of 14 initial level 2 students; a survey was conducted on each of the parents, and primary data collection was carried out to obtain authentic and accurate data for the development of this research. A quantitative approach methodology was used with a non-experimental design, suggesting that the study variables were not manipulated; it was descriptive, serving to describe the data found; the scientific method guided us to solve the problem. The data collection technique used with the parents of the children was based on a survey; through this, it allowed us to statistically analyze the data and reach the conclusion that the quality of family interactions, the active participation of parents in their children's education, and effective communication between the family and the school are determining factors that influence the cognitive development of children in this crucial stage of their formation.